Numerical investigations of the minimum-B effect in Electron Cyclotron Resonance Ion Source. (28th April 2021) - Mironov, V.; Bogomolov, S.; Bondarchenko, A.; Efremov, A.; Loginov, V.; Pugachev, D.
Abstract: The three-dimensional particle-in-cell model NAM-ECRIS is used for investigation of how the DECRIS-PM Electron Cyclotron Resonance Ion Source is reacting to changes in the source magnetic configuration. The accent is made on changes in the magnetic field at the magnetic trap center, the minimum-B value. It is calculated that the optimal normalized value of the field is ∼0.8, close to the experimental observations. The reasons for existence of the optimum are discussed. It is observed that the electron energies are increasing with the increased minimum-B values due to enhanced confinement of the energetic electrons in the plasma. Bumps in energy spectra of the radially lost electrons are observed and explained to be due to nonadiabatic losses of electrons.